Paternal Preconception Chronic Variable Stress Confers Attenuated Ethanol Drinking Behavior Selectively to Male Offspring in a Pre-Stress Environment Dependent Manner - Rompala, Gregory R.; Simons, Alison; Kihle, Brooke; Homanics, Gregg E. (Frontiers in Behavioral Neuroscience, 2018)
Stress-related psychiatric disorders such as major depression are strongly associated with alcohol abuse and alcohol use disorder. Recently, many epidemiological and preclinical studies suggest that chronic stress prior to conception has cross-generational effects on the behavior and physiological response to stress in subsequent generations. Thus, we hypothesized that chronic stress may also affect ethanol drinking behaviors in the next generation. In the first cohort of mice, we found that paternal preconception chronic variable stress significantly reduced both two-bottle choice and binge-like ethanol drinking selectively in male offspring. However, these results were not replicated in a second cohort that were tested under experimental conditions that were nearly identical, except for one notable difference. Cohort 1 offspring were derived from in-house C57BL/6J sires that were born in the animal vivarium at the University of Pittsburgh whereas cohort 2 offspring were derived from C57BL/6J sires shipped directly from the vendor. Therefore, a third cohort that included both in-house and vendor born sires was analyzed. Consistent with the first two cohorts, we observed a significant interaction between chronic stress and sire-source with only stressed sires that were born in-house able to impart reduced ethanol drinking behaviors to male offspring. Overall, these results demonstrate that paternal preconception stress can impact ethanol drinking behavior in males of the next generation. These studies provide additional support for a recently recognized role of the paternal preconception environment in shaping ethanol drinking behavior.